Rancang Bangun Sistem Informasi Tata Kelola Keuangan Komite Sekolah SMPN 1 Sedati Berbasis Website - Wicaksana, Andhika Bisma (SOTVI - Society of Visual Informatics, 2025)
SMPN 1 Sedati or commonly called SPENSASED is a junior high school located in Sedati, Sidoarjo Regency, East Java Province, Indonesia. The school has a long history of creating quality education programs for its students. Over time, SMPN 1 Sedati has become one of the fastest growing educational units and has earned the nickname Movers School. The curriculum used at SMPN 1 Sedati is an independent curriculum, which focuses on developing students' interests and talents. Not only the academic program is improved, but the extracurricular program is also very concerned. But on the other hand, the development of technology at SMPN 1 Sedati tends not to be as fast as the educational program. As an example of the topic I used, namely about Committee Financial Governance, the absence of a program that can support the performance of the staff in charge makes everything related to committee finances must be done manually and cannot be monitored in real time. In the design, the author explores further information about the main needs of the treasurer and financial staff at SMPN 1 Sedati as the main support in the system development process. The author aims to assist related parties in managing committee finances in order to create transparency and actual information.